Um caso de contratendência: baixa evasão na licenciatura em química explicada pelas disposições e integrações - Massi, Luciana; Villani, Alberto (Faculdade de Educação da Universidade de São Paulo, 2015)
Abstract This work is part of a case study of an institution in which the students had a strong sense of belonging and membership, which was reflected the low dropout rates. The course in question was the degree in chemistry of Instituto de Química (Institute of Chemistry), henceforth referred to as the IQ, of Universidade Estadual Paulista (UNESP) in Araraquara, in the State of São Paulo. We analyzed the school and academic histories of the twenty-seven students majoring in chemistry, in relation to social and academic integration, based on Vincent Tinto’s Student Integration Model (SIM). We also used the concept of habitus, originally presented by Pierre Bourdieu and revised by Bernard Lahire, in order to understand these integrations and qualitatively explain the low dropout rates, which were analyzed quantitatively. We adopted the methodology of sociological portraits, also proposed by Lahire, to analyze the interviews with the undergraduate students and their views in relation to these aspects. The portraits produced show a prevalence of educational histories that combined social and academic integration, favored by a “fit” of the previous habitus, which were updated or enhanced in the university. By focusing on a specific institution, we saw that the conditions offered by the university, which implicitly or explicitly promote the updating of various habitus in the graduate students, and which are favorable for their social and academic integration, are fundamental for explaining the low dropout rates. This fact makes this course unique, particularly due to the ways it creates ties with its students.

Resumo Este trabalho faz parte de um estudo de caso sobre uma instituição pela qual seus alunos apresentavam um forte sentimento de pertencimento e adesão, materializado em baixos índices de evasão. Trata-se da licenciatura em química do Instituto de Química (IQ) da Universidade Estadual Paulista (UNESP) de Araraquara, no interior do estado de São Paulo. Analisamos as trajetórias escolares e acadêmicas de 27 licenciandos em química, com base na Teoria da Integração do Estudante (TIE) de Vincent Tinto, quanto à integração social e acadêmica. Também utilizamos o conceito de disposição, apresentado inicialmente por Pierre Bourdieu e revisto por Bernard Lahire, para compreender essas integrações e explicar qualitativamente os baixos índices de evasão analisados quantitativamente. Adotamos a metodologia dos retratos sociológicos, também proposta por Lahire, para analisar as entrevistas dos licenciandos quanto a esses aspectos. Os retratos apontam para uma predominância de trajetos que conjugam uma integração social e acadêmica, favorecida por umencaixe das disposições anteriores atualizadas ou reforçadas na universidade. Ao investigar o caso de uma instituição específica, percebemos que as condições oferecidas pela universidade, que implícita ou explicitamente promovem a atualização de várias disposições dos licenciandos e são favoráveis à sua integração social e acadêmica, são fundamentais para explicar os baixos índices de evasão e tornam esse curso peculiar, principalmente pelas maneiras de criar vínculos com seus alunos.
A case of countertrend: low dropout rates among chemistry degree students explained by habitus and integration
Keywords: Dropout rate; Chemistry degree; Habitus; Social integration; Academic integration; Evasão; Licenciatura em química; Disposições; Integração social; Integração acadêmica